Interpersonal communication skills used by cardiologists in doctor-patient communication at the National Heart Institute, Malaysia - Govindarju, Vimala (2017)
Doctor and patient communication perceived as key component in healthcare to create positive health outcome. Somehow, interpersonal communication skills used by the doctors through verbal and nonverbal communication in health care have potential to smooth the consultations between doctors and patients. However, patients dissatisfy and communication breakdown happened between doctors and patients. The aim of this study is to look at interpersonal communication skills used by the cardiologist in doctors’ patient communication at the National Heart Institute (IJN). This study tries to understand the barriers faced by the cardiologists through their career life experience, and the strategies used to overcome the barriers in order to deliver positive health care outcome. This research applied qualitative methodology through adopting a hermeneutic phenomenological approach. The approach most appropriate to describe an understanding the meaning on phenomenon where interpersonal communication skills used by cardiologists to their patient. The researcher focused on how the cardiologists use verbal and non-verbal communication with patients, the barriers faced by the cardiologists and the strategies to overcome the barriers using interpersonal communication skills with their patients. The subject of this study are the cardiologists at IJN. About eleven cardiologists were chosen as informants through purposive sampling techniques and criterionbased selection. Data collected through in-depth interviews and observations. Instrument of the study was the researcher herself with the aid of the interview protocols. The researcher conducted the in-depth interview and observation for fifty minutes to two hours. The interviews session was audio recorded and observations captured visually. The researcher then transcribed data verbatim and analyzed it using ATLAS.ti 7 software to code the key themes, and sub-themes. Finding showed cardiologists use verbal communication with their patients by greeting and welcoming them; use multi languages which easily understand during doctor patient communication; use clear, supportive and encouraging health care information to build good relationships with patients and create a positive health outcome. The identification theme on non-verbal communication with patients are by touching them; body language and gesture; communicate using eye contact and finally use tone of voice during communicating with patients. The themes on the barriers faced by the cardiologists when they use interpersonal communication skills to their patients are doctor's attitude towards their patients, language used during the consultation and time barrier during doctors’ busy schedule in order to see patients and patients waiting hours for their appointment. Finally, in answering objective on how the cardiologists overcome the barriers, some themes were identified on the strategies to overcome the barrier on using interpersonal communication skill by the cardiologists with the patients are through communication skill; the training on communication skill and time management skill training for cardiologists. Interpersonal communication skills using verbal communication used by the cardiology doctors in IJN is highly correlated with better patients understanding on their illness and producing positive healthcare outcome. This study concludes the quality of interpersonal communication skills will influence the patient's positive healthcare outcomes. The practical implications health care providers should improvised their interpersonal communication skills with their patients because communication help the healthcare professionals to achieve intermediate outcomes in the order to gain trust, mutual understanding, adherence, social support and self-efficacy on associated with improved health. Theoretical implications on Social Cognitive Theory describe how doctors obtain and sustain positive behavioral patterns, while providing the basis for policies involvement. Evaluating behavioral change depends on the factors environment, people and behavior. SCT provides a framework for designing, implementing and evaluating by paying equal attention to the interpersonal communication skills especially verbal and nonverbal communication.